Technology as suicide risk and protective factors: from counselling point of view - Mohd Munir, Nur Syuhada; Rais, Haniza; Zubair Name, Ainol Madziah (2025)
Rising suicide rates, particularly among adolescents and marginalized groups, are causing increased interest in the development of innovative and inclusive mental health interventions. These interventions include integrating technological advances into mental health counselling. This paper focuses on one area of application for technology in counselling professional helping relationship. This research aimed at exploring association integrating technology in counsellors’ professional practices in addressing suicide behaviours. This study utilized a qualitative case study methodology to structure this research. The data were collected using semi-structured individual interviews and selected documents. Eighteen participants involved this in research. Among those include ten professional counsellors, four individuals who experienced incomplete suicide attempts, and three caregivers, all were recruited through purposive sampling. Rigorousness of the data collected were sought. Thematic analysis was employed for data analysis to extract meaningful phrases, codes, patterns, categories and themes. Findings emerged from this research include technology to be identified as one of the interferences in service delivery and technology was indicated to be among the risk factors and protective factors for suicidal behaviours. The findings underscored the need to enhance counsellors’ best practice in managing suicidal crisis issues that are critical case in Malaysia. Practical and policy recommendations related to this study are discussed.